Aminooxy acetic acid suppresses Th17-mediated psoriasis-like skin inflammation by inhibiting serine metabolism - Lee, Jong Yeong; Lee, Ji-Hyun; Lim, Hyo Jung; Kim, Eonho; Kim, Dae-Ki; Choi, Jin Kyeong (Frontiers in Pharmacology, 2023)
Background: Psoriasis is a common chronic inflammatory skin disease characterized by an external red rash that is caused by abnormal proliferation and differentiation of keratinocytes and immune T cells. This study aimed to elucidate the role of aminooxy acetic acid (AOA) in alleviating psoriasis from the perspective of immunology and metabolomics. Therefore, contributing to the development of new drugs as candidates for psoriasis treatment.To investigate the symptom-alleviating effects and the related mechanisms of AOA on the treatment of psoriasis, we used a 12-O-tetradecanoylphorbol-13-acetate-induced psoriasis-like skin mouse model and interleukin (IL)-17-stimulated human keratinocytes.The results showed that AOA ameliorated psoriasis-related symptoms and decreased inflammation-associated antimicrobial peptides and T-helper 17 (Th17)-associated cytokines in a mouse model of psoriasis. Furthermore, AOA inhibited the activation of mechanistic target of rapamycin (mTOR) by suppressing serine metabolism-related genes. Importantly, mTOR inhibition ameliorated psoriatic disease by affecting the differentiation of various T cells and normalizing the Th17/regulatory T (Treg) cell balance. In addition, IL-17-stimulated human keratinocytes showed the same results as in the in vivo experiments.Taken together, these results suggest that targeting the serine metabolism pathway in the treatment of psoriasis is a novel strategy, and that AOA could be utilized as a novel biologic to treat psoriasis.